ДИФФУЗИОНИЗМ МӘДЕНИЕТТІ ЗЕРТТЕУ ТӘСІЛІ РЕТІНДЕ (Journal of Philosophy, Culture and Political Science, 2018)
In this article the basic states of diffusion in cultural anthropology are analyzed. The elaboration of the theory of cultural ranges is considered on the basis of studying of creative work of Ratcel, Frobiniuos, Grebner.